Traditional knowledge through the generations an experiential ethnobotanical garden design using Philippine native flora in Nagtipunan, Quirino - Katigbak, Kristen Lois D.
The municipality of Nagtipunan is home to a lot of flora and fauna. It is surrounded by a natural environment with existing rivers and waterfalls. It is located high up in the vicinity of the Cagayan Valley. In order to get there, one needs to travel for several hours. Transportation and communication services are limited due to its location up in the mountain. An Agta community resides in Masog, barangay Disimungal, Nagtipuman. They rely on the knowledge and use of plants passed down through generations for their food and medicinal needs. Some of the common remedies are used for ailments like stomach aches, wounds, fevers, and such. However, because of the terrain, it can take up to several days to acquire such plants for their needs and this is a problem without direct and easy access to health care institutions. This thesis highlights ethnobotany, the scientific study of the relationship that exists between people and plants with regard to their medicinal and cultural uses ( Iwu, 2002), and documents the medicinal trees used by the Agta tribe of Masog with the intention of designing a community garden as a natural space that serves as not only a home, but also an experiential and learning site to share the knowledge of plants that is under threat of being lost to future generations. Masog as a community botanic garden will focus on growing native plants and trees that can encourage further study, enrich the knowledge, and showcase the culture of the Agta. While the traditional knowledge on plants is theirs, there is hope to minimize the threat of it being lost through time with the help of landscape architectural interventions suggested in this thesis.